Microplastics and Cardiovascular Disease - Žnidarič, Davorin; Senegačnik, Marjan (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Plastic materials are used in almost every field today. This fact brings with it a number of problems in addition to its many advantages. The causes often lie in the improper management of plastic waste, which accumulates in nature and mechanically breaks down into smaller particles Depending on the size of the particles, plastic waste is divided into macroplastics, mesoplastics and microplastics. Microplastics are particularly problematic as they are not only harmful to the environment but also to human health. Microplastics not only come from plastic waste, but microplastics are often deliberately added to certain products, such as cosmetics. Pieces of microplastics can also be released into the environment during the use of plastic products such as containers, pipes or food packaging. Microplastic fragments can enter the human body through the skin, respiratory tract or digestive tract and accumulate in various tissues, including blood and blood vessels. The topic of this paper is the problems associated with the mass use of plastics, with a particular focus on the impact of microplastics on cardiovascular diseases.